2016
DOI: 10.3758/s13414-016-1236-y
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of face gender and expression under dual-task conditions

Abstract: In order to test whether expression and gender can be attended to simultaneously without a cost in accuracy four experiments were carried out using a dual gender-expression task with male and female faces showing different emotional expressions that were backward masked by emotionally neutral faces. In the dual-facial condition the participants had to report both the gender and the expression of the targets. In two control conditions the participant reported either the gender or the expression of the face and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…However, subsequent empirical work has demonstrated that facial sex and emotion cues do interact to influence interpretation of the other. For example, work investigating cue interference (using Garner and dual task paradigms) provides a mix of evidence to suggest that the sex of a face is processed obligatorily and influences recognition of facial emotional expression (Atkinson, Tipples, Burt, & Young, 2005;García-Gutiérrez, Aguado, Romero-Ferreiro, Pérez-Moreno, 2017;Karnadewi & Lipp, 2012), and that facial emotional expressions may be processed obligatorily to influence processing of the sex of the face (Becker, 2017). Studies investigating visual after-effects have provided further evidence for the interaction between sex and emotion when processing faces (Bestelmeyer, Jones, DeBruine, Little, & Welling, 2010;Pallett & Meng, 2013).…”
Section: Characteristicsmentioning
confidence: 99%
“…However, subsequent empirical work has demonstrated that facial sex and emotion cues do interact to influence interpretation of the other. For example, work investigating cue interference (using Garner and dual task paradigms) provides a mix of evidence to suggest that the sex of a face is processed obligatorily and influences recognition of facial emotional expression (Atkinson, Tipples, Burt, & Young, 2005;García-Gutiérrez, Aguado, Romero-Ferreiro, Pérez-Moreno, 2017;Karnadewi & Lipp, 2012), and that facial emotional expressions may be processed obligatorily to influence processing of the sex of the face (Becker, 2017). Studies investigating visual after-effects have provided further evidence for the interaction between sex and emotion when processing faces (Bestelmeyer, Jones, DeBruine, Little, & Welling, 2010;Pallett & Meng, 2013).…”
Section: Characteristicsmentioning
confidence: 99%